Quantitative MR imaging and spectroscopy of brain tumours: a step forward? - Wagnerova, Dita; Herynek, Vit; Malucelli, Alberto; Dezortova, Monika; Vymazal, Josef; Urgosik, Dusan; Syrucek, Martin; Jiru, Filip; Skoch, Antonin; Bartos, Robert; Sames, Martin; Hajek, Milan (European radiology, 2012)
OBJECTIVES: A prospective quantitative MR study of brain tumours was performed to show the potential of combining different MR techniques to distinguish various disease processes in routine clinical practice. METHODS: Twenty-three patients with various intracranial tumours before treatment (diagnosis confirmed by a biopsy) and 59 healthy subjects were examined on a 3-T system by conventional MR imaging, 1H spectroscopic imaging, diffusion tensor imaging and T2 relaxometry. Metabolic concentrations and their ratios, T2 relaxation times and mean diffusivities were calculated and correlated on a pixel-by-pixel basis and compared to control data. RESULTS: Different tumour types and different localisations revealed specific patterns of correlations between metabolic concentrations and mean diffusivity or T2 relaxation times. The patterns distinguish given tissue states in the examined area: healthy tissue, tissue infiltrated by tumour, active tumour, oedema infiltrated by tumour, oedema, etc. This method is able to describe the complexity of a highly heterogeneous tissue in the tumour and its vicinity, and determines crucial parameters for tissue differentiation. CONCLUSIONS: A combination of different MR parameters on a pixel-by-pixel basis in individual patients enables better identification of the tumour type, direction of proliferation and assessment of the tumour extension. KEY POINTS: • Magnetic resonance offers many different methods of examining the brain. • A combination of quantitative MR parameters helps distinguish different brain lesions • Different tumour types revealed specific correlation patterns amongst different MR parameters • The correlation patterns reflect highly heterogeneous complex tissue within tumours.
Keywords: Magnetic Resonance Imaging; nádory mozku; Biopsy; mozek; magnetická rezonanční tomografie; Humans; Case-Control Studies; lidé středního věku; mapování mozku; Brain Neoplasms; studie případů a kontrol; Female; Aged; dospělí; Edema; senioři; lidé; magnetická rezonanční spektroskopie; počítačové zpracování obrazu; Image Processing, Computer-Assisted; biopsie; zobrazování difuzních tenzorů; Brain Mapping; Adult; difuze; ženské pohlaví; Diffusion; Diffusion Tensor Imaging; edém; Male; Middle Aged; Brain; gliom; Magnetic Resonance Spectroscopy; mužské pohlaví; Glioma